2021
DOI: 10.1007/s10784-021-09542-7
|View full text |Cite
|
Sign up to set email alerts
|

Domestic and international climate policies: complementarity or disparity?

Abstract: Climate change is a global crisis that requires countries to act on both domestic and international levels. This paper examines how climate policies in these two arenas are related and to what extent domestic and international climate ambitions are complementary or disparate. While scholarly work has begun to assess the variation in overall climate policy ambition, only a few studies to date have tried to explain whether internationally ambitious countries are ambitious at home and vice versa. According to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The poor parallel between domestic and international policies, as depicted in our indexes, corresponds to broader searches for external validity among domestic climate policy measures. While international agreement ratification is widely recognized as the best indicator of a nation's international environmental policy stringency [38,42,66], there is no such consensus, even in the NDCs of nations, of what constitutes a stringent domestic climate policy. Economists have highlighted the importance of a carbon tax or emissions trading system [67] and the centrality of "Green New Deal" government spending (see for example [68] on US and [69] on Europe).…”
Section: Discussion and Subsample Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The poor parallel between domestic and international policies, as depicted in our indexes, corresponds to broader searches for external validity among domestic climate policy measures. While international agreement ratification is widely recognized as the best indicator of a nation's international environmental policy stringency [38,42,66], there is no such consensus, even in the NDCs of nations, of what constitutes a stringent domestic climate policy. Economists have highlighted the importance of a carbon tax or emissions trading system [67] and the centrality of "Green New Deal" government spending (see for example [68] on US and [69] on Europe).…”
Section: Discussion and Subsample Analysismentioning
confidence: 99%
“…Extending this reasoning, we argue that nations may be more willing to join international agreements after other leading nations have already "gotten out front" as a justification for the timing of a nation's signing and ratification as a component of the index. We use a range of environmental agreements to construct this variable from the 1980s and early 1990s, agreeing with [42] that a nation's foreign policy identity, with a few notable exceptions, changes slowly, even if national governments change more frequently. The Paris Agreement was excluded from our sample for two reasons.…”
Section: International and Domestic Climate Policy Stringency: Defini...mentioning
confidence: 99%
“…Hence, research on the mechanisms of domestic and international climate finance policies are on the rise. For instance, some previous studies have investigated the influence of bureaucratic agencies on climate finance allocation (Peterson & Skovgaard, 2019), coastal adaption project design patterns and contributions (Kuhl et al, 2020), economic impacts of climate actions between countries (Román et al, 2019), climate mainstreaming (Bhandary, 2021), the complementarity or disparity between domestic and international climate policies (Peterson, 2021), the impact of self-regulation in the adoption of the Equator Principles (Contreras et al, 2019), and the moderating role of politics and the media in climate investment decisions (Bae et al, 2021;Pickering & Mitchell, 2017). It is observed that past studies have focused on the barriers, strategies, and the impact of climate finance at both domestic and international levels.…”
Section: Domestic and International Climate Finance Policiesmentioning
confidence: 99%
“…Climate change in border regions has also challenged the frame on territorial borders, which as opposed to the flow of goods and capital, climate change is considered an extraterritorial issue and cannot be managed by border laws and regulations. Therefore, the formation of a deep stream of knowledge in theories of international relations is necessary to solve the challenges of climate change (Benzi & Persoon, 2019) which in other words is addressed as one of the main issues of modern climate policy (Peterson, 2021). The core issue leading to border disputes between the neighboring countries is a lack of consensus on the prime cause (climate change or human intervention) of water depletion in border rivers, which is a main objective of this study.…”
mentioning
confidence: 99%